(untitled) (Praxis Educativa, 2022)
The objective of this work is to present an analysis of two discourses that would build the curriculum issued by the Ministry of Education of the Nation during the government of Mauricio Macri, to uncover these hidden areas, those knowledges and relationships that provide their conditions of possibility and allow us understand why certain rules, concepts, practices and other modes of relationship among subject, education and teaching were established. It tries to ask us: what are the foundations of the new curriculum and what is left of it? What education and what teaching was designed and for which discipline? In other words, it is about understanding the discourses that establish or sense two curricular documents, or the place that the subject occupies, or teach and education.